Effect of methanol-organosolv pretreatment on anaerobic digestion of lignocellulosic materials. (May 2021) - Oliva, A.; Tan, L.C.; Papirio, S.; Esposito, G.; Lens, P.N.L.
Abstract: Lignocellulosic materials are the most abundant biomass on the planet, representing a great opportunity for energy valorisation. This work investigated the effect of methanol-organosolv pretreatment on the methane production from hazelnut skin (HS), spent coffee grounds (SCG), and almond shell (AS). The pretreatment on the three lignocellulosic materials was performed at 130, 160, and 200 °C for 60 min using a 50% ( v/v ) methanol solution, with and without the addition of sulfuric acid as a catalyst. The biomethane potential of raw and pretreated substrates was evaluated under wet-mesophilic conditions in batch reactors, achieving 17.3 (±32.3), 293.4 (±46.6), and 23.2 (±9.6) mL CH4 /g VS for HS, SCG, and AS, respectively. The methanol-organosolv pretreatment was particularly effective on HS, increasing its biomethane potential up to 310.6 (±22.2) CH4 /g VS. On the contrary, all pretreatment conditions were ineffective on SCG and AS in terms of cumulative methane production. Among the three substrates, only HS showed significant composition changes due to the pretreatment, with the lignin content decreasing from 39.66 to 34.73% and the amount of bioavailable sugars increasing. An energy assessment confirmed the pretreatment efficacy on HS, with a maximum net positive energy recovery of 1.35 kWh/kg VS. Graphical abstract: Image 1 Highlights: CH4 potential of hazelnut skin, spent coffee grounds and almond shell was evaluated. Organosolv pretreatment increased hazelnut skin biomethane potential up to 18-fold. 310.6 mL CH4 /g VS was obtained from hazelnut skin pretreated at 130 °C with catalyst. Energy recovery from pretreated hazelnut skin achieved a value of 1.35 kWh/kg VS. Spent coffee grounds and almond shell produced 322.9 and 24.8 mL CH4 /g VS.